I am studying AES and trying to implement it. But I have a hard time understanding the passage of the mixing column. In that step we have to perform matrix multiplication between the state matrix and another fixed matrix. Here is the example given in the material I am studying:
I'm not getting the
03*2F part. How did it become
(02*2F)xor2F? Is the material correct or does it have an error?
I have it
3 = 2 xor 1 Thus
3 x 2F = (2 xor 1) x 2F = (2 x 2F) xor 2F but what if 4 x 2F?
4 = 2 xor 6 so
(2 xor 6) x 2F and that?